2073 [videorecording (Blu-Ray)] - Grisoni, Tony; Kapadia, Asif, 1972-; Ackie, Naomi; Morton, Samantha; Hewer, Hector (Neon, 2025)
It's 2073, and the worst fears of modern life have been realized. Surveillance drones fill the burnt orange skies and militarized police roam the wrecked streets, while survivors hide away underground. Interconnecting today's global crises of authoritarianism, unchecked big tech, inequality, and global climate change, 2073 is an unshakable vision of a future that could very well be our own.